Regional Policy in Greece: An Overview and the Recent Policy Change - George Petrakos; Yannis Psycharis (European Regional Science Association (ERSA), 2006)
This paper provides a broad overview of the most recent changes in regional policy in Greece. It is structured in six sections. After this introduction, the second section reviews the Greek regional problem and considers different approaches to understanding and perceiving it. The third section provides an overview of the recent key regional policy changes. The fourth section then focuses on changes to different components of regional policy i.e. regional incentives, regional programmes and the regional allocation of public investment. The fifth section discusses changes in the implementation and delivery of regional policy. The sixth section summaries the regional policy changes in Greece during the recent period.
Keywords: 330